Purī, yā, Purushottama kshetra - Rath Śarmā, Sadāśiva, 1921- (Śrī Jagannātha Aitihāsika Gaveshaṇā Samiti, 1955)
History and mythology of Puri, description of the Jagannath Temple and other Hindu pilgrimage centers at Puri.